Evaluation of Productive Learning Programs in Areas of Expertise Computer and Network Engineering In Vocational High Schools - Yosi Nofita Sari; Ambiyar Ambiyar; Dedy Irfan; Waskito Waskito (EDUTEC : Journal of Education And Technology, 2022)
Sekolah Menengah Kejuruan (SMK) is one of the educational institutions that aims to prepare students to become skilled workers according to competence. This study aims to evaluate productive learning programs in the field of expertise in Computer and Network Engineering at SMK Negeri 8 Padang learning. This study used the evaluation model of the stake countenance program (antecedents, transactions and outcomes) with a combination research method (Mixed Methods) with a sequential explanatory design model. The respondents of the study were class XI students in the field of Computer and Network Engineering expertise of SMK Negeri 8 Padang a total of 63 people, teachers of productive subjects of Network Service Technology, deputy head of curriculum, head of the department of Computer and Network Engineering (TKJ) expertise. Data collection techniques use observation, questionnaires, documentation and interviews. Data analysis techniques for quantitative data use percentage analysis, for qualitative data in analysis with data collection, data reduction, data presentation and conclusion / verification. Merging is done to determine mutually reinforcing or conflicting data and deepen the data findings. The results showed that the implementation of productive learning programs in the field of Computer and Network Engineering expertise at SMK N 8 Padang when viewed from the antecedents component has a percentage of 78.5% in the sufficient category. The transaction stage has a percentage of 79.48% in the sufficient category and the outcomes component has a percentage of 76.7% in the sufficient category. Based on the results of the research above, it can be seen that the achievement of productive learning programs in the field of Computer and Network Engineering expertise at SMK Negeri 8 Padang is still in the sufficient category. Therefore, it is necessary to make improvements and optimizations in each component element.